Global trends in the burden of ischemic heart disease based on the global burden of disease study 2021: the role of metabolic risk factors - Yifei Wang; Qing Li; Lei Bi; Bin Wang; Tingting Lv; Ping Zhang (BMC Public Health)
Abstract Background Ischemic heart disease (IHD) remains a leading cause of mortality and morbidity globally. This study aims to evaluate the trends in IHD burden across different socioeconomic regions using data from the Global Burden of Disease Study 2021 (GBD 2021) and to understand the impact of the metabolic risk factors on these trends. Methods Data from GBD 2021 was analyzed to evaluate the global age-standardized death rates (ASDR) and disability-adjusted life years (ASRDALYs) linked to IHD. Key metabolic risk factors evaluated included high systolic blood pressure (SBP), low-density lipoprotein cholesterol (LDLc), fasting plasma glucose (FPG), and body mass index (BMI). Temporal trends were assessed using estimated annual percentage changes (EAPCs), with further analysis by age, sex and socio-demographic index (SDI). Results Resource-abundant regions showed notable reductions in ASDR and ASRDALYs, largely due to effective management of SBP and LDLc, resulting in an EAPC of -3.43 (95% CI: -3.32, -3.53). In contrast, resource-limited regions, particularly among males, experienced stagnation or even increases in IHD burden. The EAPC of ASDR in low-, low-middle-, and middle-SDI regions ranged from − 0.12 (95% CI: -0.04, -0.19) to 0.16 (95% CI: 0.09, 0.23). Among males, the values ranged from 0.22 (95% CI: 0.14, 0.29) to 0.55 (95% CI: 0.47, 0.62). The increase in IHD burden in these regions was primarily driven by rising levels of FPG and BMI. Younger populations (15–49 years) were disproportionately affected, showing increasing exposure to these metabolic risks. Conclusion Regional disparities in IHD burden persist, primarily driven by metabolic risk factors. Resource-abundant regions have benefitted from effective control of SBP and LDLc, whereas resource-limited regions face growing challenges, especially related to FPG and BMI. The use of secondary data from the GBD 2021 database provides a comprehensive global perspective but may not fully capture local variations in disease burden. Targeted public health strategies and early interventions are essential to reduce the growing IHD burden in these vulnerable populations.